2008
DOI: 10.1002/bies.20708
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D discovery outpaces FDA decision making

Abstract: The US FDA currently encourages the addition of vitamin D to milk and cereals, with the aim of reducing rickets in children and osteoporosis in adults. However, vitamin D not only regulates the expression of genes associated with calcium homeostasis, but also genes associated with cancers, autoimmune disease, and infection. It does this by controlling the activation of the vitamin D receptor (VDR), a type 1 nuclear receptor and DNA transcription factor. Molecular biology is rapidly coming to an understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 78 publications
0
86
0
Order By: Relevance
“…One group (TG Marshall, Autoimmunity Research Foundation, Thousand Oaks, CA) has recommended and continues to recommend lowering vitamin D status to treat a number of chronic inflammatory conditions (Marshall 2008). The basis for this recommendation are the reports of production of 1,25(OH) 2 D 3 by the immune system during disease pathology and the possibility that this induction of 1,25(OH) 2 D 3 may be contributing to diseases from obesity to other chronic diseases including those mediated by Th1 cells like sarcoidosis and Crohn's disease (Marshall et al 2004;Marshall 2008).…”
Section: Extra-renal Production Of the 1alpha Hydroxylasementioning
confidence: 99%
See 1 more Smart Citation
“…One group (TG Marshall, Autoimmunity Research Foundation, Thousand Oaks, CA) has recommended and continues to recommend lowering vitamin D status to treat a number of chronic inflammatory conditions (Marshall 2008). The basis for this recommendation are the reports of production of 1,25(OH) 2 D 3 by the immune system during disease pathology and the possibility that this induction of 1,25(OH) 2 D 3 may be contributing to diseases from obesity to other chronic diseases including those mediated by Th1 cells like sarcoidosis and Crohn's disease (Marshall et al 2004;Marshall 2008).…”
Section: Extra-renal Production Of the 1alpha Hydroxylasementioning
confidence: 99%
“…The basis for this recommendation are the reports of production of 1,25(OH) 2 D 3 by the immune system during disease pathology and the possibility that this induction of 1,25(OH) 2 D 3 may be contributing to diseases from obesity to other chronic diseases including those mediated by Th1 cells like sarcoidosis and Crohn's disease (Marshall et al 2004;Marshall 2008). The argument is that the hormone activity of 1,25(OH) 2 D 3 induces transcription of a large number of genes that somehow cause these diseases and that 1,25(OH) 2 D 3 should be measured because it is the biologically active form of vitamin D that binds the receptor (Marshall 2008). Current assays for 25(OH)D3 that are used to assess vitamin D levels in the general population are inaccurate and lack standards (Glendenning et al 2006).…”
Section: Extra-renal Production Of the 1alpha Hydroxylasementioning
confidence: 99%
“…38 This work suggested that microbes may be able to directly alter VDR ligand binding pocket occupancy, and subsequently VDR expression, in order to gain a survival advantage.…”
Section: Communities Of Microbes Drive Autoimmune Diseasementioning
confidence: 99%
“…However, this drug has a unique affinity for the VDR nuclear receptor, for which it is most probably a partial agonist. 38,77 In order to be effective in this targeting, the dosing has to be more frequent as the VDR's half-life is only 4-6 h before it is broken apart by caspase-3, and protease activity. 78 Thus, when dosed at 4-to 8-h intervals, VDR stimulation persists between doses.…”
Section: Our Therapeutic Approachmentioning
confidence: 99%
See 1 more Smart Citation